Quatro Décadas de Transformações: A vilegiatura marítima no litoral metropolitano de Fortaleza, Ceará – Brasil - Prof. Dr. Alexandre Queiroz Pereira (Confins)
The coastal urbanization and the maritime summer vacation are crucial themes to the urban geography studies in the Northeast region. This theoretic-methodological undertaking in the form of an article aims to comprehend the production of modern maritime spatialities in the metropolitan coastal spaces of Fortaleza during the last four decades. In order to do so, the case of the metropolitan peri-urban space of Fortaleza has been analyzed with focus on the network of appropriate coastal places to perform summer vacation activities. The examination of maritime summer vacation is indicated as a vector of metropolization and internationalization. This document is the result of diverse methodological practices (descriptive, analytical and explicative) established in documental and bibliographical research, and on field observations. The highlighted maritime practice is one of the multiple syntheses of the urbanization process, and its investigation contributes to the understanding of the contemporary urban way of life. Considering the locational advantages historically produced, the process consolidates the urbanization of the metropolitan coastal space in Fortaleza. Therefore, the northeastern metropolis lays emphasis on its coastal condition and becomes well-known for the maritime practices it holds.